2020
DOI: 10.1080/20008198.2020.1807170
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial mechanisms of change in symptoms of Persistent Complex Bereavement Disorder amongst refugees from Myanmar over the course of Integrative Adapt Therapy

Abstract: Background: The ability to adapt to the psychosocial disruptions associated with the refugee experience may influence the course of complicated grief reactions. Objective: We examine these relationships amongst Myanmar refugees relocated to Malaysia who participated in a six-week course of Integrative Adapt Therapy (IAT). Method: Participants (n = 170) included Rohingya, Chin, and Kachin refugees relocated to Malaysia. At baseline and six-week post-treatment, we applied culturally adapted measures to assess sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For example, Hossain A K M et al, 2020 conducted a cross-sectional survey among Rohingya refugees in Bangladesh. Six of the included articles were intervention studies (A. K. Tay et al, 2019;Mahmuda et al, 2019;Tarannum et al, 2019;Tay, Khat Mung, et al, 2020;Tay et al, 2021). For example, Tarannum et al, 2019 reported the findings from an intervention study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hossain A K M et al, 2020 conducted a cross-sectional survey among Rohingya refugees in Bangladesh. Six of the included articles were intervention studies (A. K. Tay et al, 2019;Mahmuda et al, 2019;Tarannum et al, 2019;Tay, Khat Mung, et al, 2020;Tay et al, 2021). For example, Tarannum et al, 2019 reported the findings from an intervention study.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies (n = 16) were conducted in Bangladesh (Zaman et al, no date;Riley et al, 2017Tarannum et al, 2019;Wells et al, 2019;Mahmuda et al, 2019;Christensen, Ahsan and Mandal, 2020;Hossain et al, 2020Tay et al, 2021;Haque, 2021b, 2021a;O'connor and Seager, 2021;Awang, Mohamad and Maria Awaluddin, 2022;Palit et al, 2022), for example, Wells et al, 2019 conducted a qualitative study on Rohingya refugees, living in the camps, whereas some studies (n = 8) were conducted in Malaysia (A. K. Tay et al, 2019;Alvin Kuowei Tay et al, 2019;Shaw et al, 2019;Welton-Mitchell et al, 2019;Kaur et al, 2020;Tay, Khat Mung, et al, 2020;Tay et al, 2022), such as a cross sectional study by Tay et al, 2019.…”
Section: Countrymentioning
confidence: 99%
See 1 more Smart Citation
“…These numbers are predicted to increase (Maretti et al, 2019;Marsella & Ring, 2003). Mental health issues that may arise from experiences related to forced displacement include anxiety disorders, post-traumatic stress reactions, somatic complaints, depression, and complex grief reactions (Munz & Melcop, 2018;Shannon et al, 2015;Tay et al, 2020). Among circa 40% of refugee children, traumatizing experiences along the way to seek refuge have had a severe effect on the children's interpersonal skills (Baron & Flory, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition to the abovementioned factors, key predictors of treatment response in refugee populations that warrant attention are gender, age, time since arrival, premigration trauma, access to support and resources, residency status, access to employment, social relations, baseline symptom severity, length of functional impairment, comorbidities and chronic pain. [16][17][18] None of these predictors have been consistently replicated across studies and settings, but should be considered in future studies.…”
mentioning
confidence: 99%